Smoke-free-school-hours at vocational education and training schools in Denmark: attitudes among managers and teaching staff - a national cross-sectional study - Clara Heinze; Anneke Vang Hjort; Peter Elsborg; Helle Terkildsen Maindal; Charlotte Demant Klinker (BMC, 2019)
Abstract Background Tobacco is the main cause of non-communicable disease and premature death globally. Implementing restrictive school tobacco policies such as smoke-free-school-hours (SFSH) may have the potential to reduce smoking among Vocational Education and Training (VET) school students. To be effective, school tobacco policies that largely involve strict and consistent enforcement by both managers and teaching teaching staff must be implemented. This study investigated the attitudes towards the implementation of SFSH among the managers and teaching staff at Danish VET schools. Methods The analyses were based on cross-sectional survey data collected with an online survey among managers and teaching staff at Danish VET schools. The data was collected from March to June 2017. Results Managers and teaching staff (n = 571) from 71 out of 87 Danish VET schools (81.6%) took part in the survey. In the adjusted analysis, teaching staff were twice as likely as managers to have a favourable attitude towards SFSH. Furthermore, being female and of increasing age correlated with having a favourable attitude. A trend towards schools in favour of SFSH having more health promotion facilities, policy and practice, was identified. Conclusion and implications Existing health promotion facilities and activities at the schools were associated with a favorable attitude among the management towards implementing SFSH. Thus, implementing other health promotion activities and policies might be an important first step to establish readiness to implement SFSH.